Towards virtualization : open and distance learning - Venugopal Reddy, V.; Manjulika, S. (New Delhi : Kogan Page India, 2002)
Contributed articles.
Includes bibliographical references and index.
Keywords: Distance education; Open learning; Information technology -- Social aspects